(@kursusarab) تحليل محتوى تعليم اللغة العربية في تطبيق تيك توك على حساب - Siti Nursina; Fatma Yulia (Academy of Education Journal, 2024)
Innovative learning has been widely encountered today due to the accelerating development of technology, one of which is application-based learning. Tiktok is an application that is being loved by the world community, even one of them is the Indonesia people, this allows users to access various information and entertainment delivered in short videos. So this study aims to find out what Arabic learning content is created and shared by the content creator studied, namely on @kursusarab account. Whether there is a pattern in the content created and shared by content creators in Arabic learning content and what kind of language learning content is most interesting and liked by TikTok users in learning Arabic that will be seen based on the highest engagement from the number of viewers, Most likes/likes for each pattern or type of learning content from @kursusarab creators. The method used in this study is a qualitative research method with an analysis method, namely content analysis. The results in this study show that the use of the tiktok application as a form of application-based Arabic learning gets a positive response from other tiktok users, this is reviewed from the number of engagements received from @kursusarab creators with a total of 2.1 million viewers and 456.1 thousand likes/likes on the content of the song "see my garden" in Arabic.